Simulation-based optimization for urban transportation demand management strategy. (July 2018) - Yao, Baozhen; Yan, Qianqian; Chen, Qian; Tian, Zhihui; Zhu, Xuefeng
Transportation demand management (TDM) is one of the important methods for solving the problem of increasingly severe urban traffic congestion. This paper proposes a bi-level model to optimize urban TDM strategies based on simulation. The upper level is the TDM strategy optimization model, searching for the optimal TDM strategy. The lower level is a traffic assignment model based on the simulation, assigning traffic flow to multimodal transport networks according to the candidate TDM strategies. A heuristic algorithm is also defined and implemented to optimize TDM strategies. Based on VISSIM simulation, the optimization for TDM strategies proposed in this paper is validated with the research area of Harbor Square–San Ba Square–Er Qi Square in Dalian in China. The results show that the optimization of urban TDM strategies can effectively alleviate urban traffic congestion. It provides a scientific decision basis for urban TDM policy.